Impact of BRAC reproductive health and disease control programme on different health services utilisation - Karim, Fazlul; Tripura, Abhilash; Gani, Md. Showkat (BRAC Research and Evaluation Division (RED), 2019)
This study assessed the impact of BRAC's RHDC programme on different health services utilisation compared to the baseline status as well as the comparison area. In the baseline study (199:.?.) fertility and mortality data were collected from 12,073 households (programme 8,072 and comparison 4,001) representing a total of 261 villages (programme 184 and comparison 77). But, in the follow-up study clone in 2000, 103 villages (programme 80 and comparison 23) were revisited. Using the cluster survey method, data were collected from 8,033 households (programme 4,003 and comparison 4,030) in the follow-up study. The programme villages were drawn from Bogra and Dinajpur districts whilst the comparison villages from Jaipurhat district. It is to be noted that for measuring the level of different health service use data were collected from toe;~ and 25% of the total households covered for mortality and fertility estimate during the baseline and the follow-up studies respectively, because measurement of other service utilisation required lesser number of sample than the mortality and fertility estimates. However, the following sections present the key findings of the study.